PENINGKATAN PENGETAHUAN PENTINGNYA HIGIENE DAN SANITASI UNTUK KESELAMATAN KERJA PENJAMAH MAKANAN MELALUI KEGIATAN POSTER EDUCATION DI PONDOK PESANTREN - amilia, Amilia Yuni Damayanti; Aisha Widyadana Abidin; Ananda Annisa; Siti Ummisah; Ineyza Regianti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Personal protective equipment is personal protective equipment that is used to protect oneself from accidents while working. According to observations made of food handlers in the kitchen of Darussalam Gontor University (UNIDA Gontor) Female Campus, there are workers who comply with the use of PPE when working when making or cooking food or when cleaning the kitchen, but there are still some workers who do not use PPE. can be harmful to workers, fiber can affect food sanitation hygiene. Hygiene is the science that deals with health problems and various efforts to maintain or improve health. Sanitation is a disease prevention effort that focuses on human environmental health activities. This activity uses the pre-test post-test method with workers in the kitchen at UNIDA Gontor Female Campus who are the respondents. Sampling of activities, namely the food handlers at the Kitchen of UNIDA Gontor Female Campus. Keywords: PPE, food handler, knowledge, hygiene, sanitation